EKSPLORASI DAN EFEKTIVITAS JAMUR PATOGEN SERANGGA SEBAGAI AGENS HAYATI DARI RHIZOSFER BERBAGAI PERTANAMAN PERTANIAN ASAL DATARAN RENDAH OGAN KOMERING ILIR (Universitas Muhammadiyah Palembang, 2022)
Insect pathogenic fungi are environmentally friendly pest control agents. This study aims to explore insect pathogenic fungi from the rhizosphere of various crops. The study was conducted in the Pest and Plant Diseases laboratory, Faculty of Agriculture, University of Palembang, in February-May 2019. The study used a factorial Completely Randomized Design (CRD) consisting of 3 replications and 15 treatments. The research stage is exploration using Omphisa fuscidentalis larvae. The soil for trapping insect pathogenic fungi comes from lowland rice, long beans, and rubber plantations in the Ogan Komering Ilir district. Isolation and identification of the fungus using the fungus that comes out of the larval body cultured on PDA (Potato Dextrose Agar) media, incubated for 7 days at room temperature. Observation of mortality of O. fuscidentalis larvae for 15 days. The first observation was 3 days after the infestation (hsi) with an interval of 3 days of observation. Data were analyzed descriptively, displayed in the form of images, mortality data were analyzed using Diversity Analysis. The results of the study found three genera of insect pathogenic fungi, namely Beauveria bassiana, Metarhizium anisopliae and Aspergillus sp. The highest larval mortality percentage was in the A3T15 treatment of 10.02% and the lowest in A2T3 and A3T3 was 0.71%. The highest mortality time of larvae was at T15 of 23.86%, and the lowest was at T3 of 3.81%. Efforts to obtain more specific and effective strains of insect pathogenic fungi, further research needs to be done on a laboratory and field scale.